2017
DOI: 10.1002/humu.23154
|View full text |Cite
|
Sign up to set email alerts
|

Assessment ofTP53Polymorphisms andMDM2SNP309 in Premenopausal Breast Cancer Risk

Abstract: Germline polymorphic variants in cancer predisposition genes such as TP53 have been shown to impact the risk of premenopausal cancer. Accordingly, the aim of this study was to assess the spectrum of polymorphisms in TP53 and its negative regulatory gene, MDM2 (SNP309:T>G) in patients with premenopausal breast cancer. Our findings in a cohort of 40 female patients demonstrate no significant correlation between the studied polymorphisms and risk of premenopausal breast cancer. Although one polymorphism is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
(27 reference statements)
0
4
0
1
Order By: Relevance
“…For example, loss of function due to mutations in tumour suppressor genes (like TP53 [Tumour protein p53]), can lead to cancer and its progression. Replacement of mutated genes with the functional version of TP53 can inhibit the growth of breast cancer tumours and induce apoptosis 61,88 …”
Section: Gene Therapy Strategies For Bc Treatmentmentioning
confidence: 99%
“…For example, loss of function due to mutations in tumour suppressor genes (like TP53 [Tumour protein p53]), can lead to cancer and its progression. Replacement of mutated genes with the functional version of TP53 can inhibit the growth of breast cancer tumours and induce apoptosis 61,88 …”
Section: Gene Therapy Strategies For Bc Treatmentmentioning
confidence: 99%
“…The connections between coilin and cancer have not been systematically assessed. In recent years, the associations of SNPs and disease risks have been demonstrated in many studies [22][23][24]. Here, we performed clinical bioinformatic analysis and found that coilin mutation at residue 121 or 145 is rare in patients of various cancer types.…”
Section: Discussionmentioning
confidence: 86%
“…In recent years, large-scale sequencing projects to determine the SNPs of various human populations throughout the globe have been carried out [ 19 , 20 , 21 ]. Evidence has shown that SNP is one of the potential factors that determine the risk of hundreds of diseases, including cancers [ 22 , 23 , 24 ]. Among the SNP types, the nonsynonymous (missense) SNPs have the highest probability of affecting protein functions, changing cell phenotypes, and resulting in diseases [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, she was diagnosed at the very young age of 32 with HER2-enriched breast cancer and had a first-degree family history, with a mother affected by uterine sarcoma and a father by hepatocellular carcinoma. However, other studies focusing on the premenopausal population underline that early-onset breast cancer cannot be attributed to TP53 polymorphisms alone, although specific mutations occur in this young cohort in higher frequency, without, however, always affecting p53 transactivation function [ 45 ]. Concerning CHEK2 , we identified by a targeted gene sequencing panel three premenopausal patients who carried germline pathogenic mutations that affect the expression of this key cell cycle checkpoint kinase.…”
Section: Discussionmentioning
confidence: 99%